Keynesian economics (Henry Stewart Talks, 2025)
The General Theory's impact, Classical vs. Keynesian economics, Aggregate demand drives output, Government intervention in policy, The multiplier effect & limits, Post-WWII Keynesian policy adoption, Debate: govt. intervention vs. markets, Modern Keynesian crisis response